Regulation of Sulfotransferase and UDP-Glucuronosyltransferase Gene Expression by the PPARs - Melissa Runge-Morris; Thomas A. Kocarek (PPAR Research)
During phase II metabolism, a substrate is rendered more hydrophilic through the covalent attachment of an endogenous molecule. The cytosolic sulfotransferase (SULT) and UDP-glucuronosyltransferase (UGT) families of enzymes account for the majority of phase II metabolism in humans and animals. In general, phase II metabolism is considered to be a detoxication process, as sulfate and glucuronide conjugates are more amenable to excretion and elimination than are the parent substrates. However, certain products of phase II metabolism (e.g., unstable sulfate conjugates) are genotoxic. Members of the nuclear receptor superfamily are particularly important regulators of SULT and UGT gene transcription. In metabolically active tissues, increasing evidence supports a major role for lipid-sensing transcription factors, such as peroxisome proliferator-activated receptors (PPARs), in the regulation of rodent and human SULT and UGT gene expression. This review summarizes current information regarding the regulation of these two major classes of phase II metabolizing enzyme by PPARs.